2018
DOI: 10.1002/pssa.201701065
|View full text |Cite
|
Sign up to set email alerts
|

Quantized Electron Transport Through Graphene Nanoconstrictions

Abstract: Here, the quantization of Dirac fermions in lithographically defined graphene nanoconstrictions is studied. Quantized conductance is observed in single nanoconstrictions fabricated on top of a thin hexamethyldisilazane layer over a Si/SiO2 wafer. This nanofabrication method allows to obtain well defined edges in the nanoconstrictions, thus reducing the effects of edge roughness on the conductance. The occurrence of ballistic transport is proved and several size quantization plateaus are identified in the condu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 60 publications
1
10
2
Order By: Relevance
“…This method led to a substantial increase of the charge mobility which also remained high for a long period of time (~96 h). Quantized conductance at zero magnetic field was also observed in refs 12,13 , but only in the form of kinks , suggesting that the edge definition and roughness control was not sufficiently high. In this contribution we propose a novel cryo-etching method theat enables us to overcome the above mentioned problems and fabricate nanoconstrictions with both very high charge carrier mobility and unprecedented quality of the structure edges.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…This method led to a substantial increase of the charge mobility which also remained high for a long period of time (~96 h). Quantized conductance at zero magnetic field was also observed in refs 12,13 , but only in the form of kinks , suggesting that the edge definition and roughness control was not sufficiently high. In this contribution we propose a novel cryo-etching method theat enables us to overcome the above mentioned problems and fabricate nanoconstrictions with both very high charge carrier mobility and unprecedented quality of the structure edges.…”
Section: Introductionmentioning
confidence: 78%
“…Well-defined conductance plateaus could not be observed because of the roughness of the heterostructure’s edges and the planar structure itself (the latter resulting from the intrinsic dielectric behavior of the hBN films). These problems were partially overcome by fabricating NCs from exfoliated graphene on hydrophobic silicon oxide substrates with the use of hexamethyldisilazane (HMDS) 12,13 . This method led to a substantial increase of the charge mobility which also remained high for a long period of time (~96 h).…”
Section: Introductionmentioning
confidence: 99%
“…This result, supported by the remarkable agreement with theoretical calculations using realistic profiles of the edge roughness, is a clear indication of ballistic transport due to the very high mobility and smooth edges that arise from the novel use of the cryo-etching procedure in their preparation. The estimated value of t in our structure is also significantly higher than the one obtained in much narrower NCs of width W = 100 nm produced by means of a HMDS treatment [100,101] and reported in the previous section. In these samples, low-roughness edges are generated mainly due to the fact that the etching process on a single layer graphene is more controllable and a clean edge on a single layer of material is easier to attain than the one obtained on a thicker encapsulated graphene nanostructure.…”
contrasting
confidence: 68%
“…We have fabricated GNCs [100] through electron beam litography of mechanical exfoliated graphene flakes transferred to Si/SiO2 wafers treated before and after the exfoliation with hexamethyldisilazane, following a similar procedure to the one used by Caridad et al [101]. Details on the fabrication process can be found in section 3.1.1.…”
Section: Transport Measurements On Graphene Nanoconstrictions (Gncs) mentioning
confidence: 99%
“…In this context, Muñoz-Rojas et al found numerically that coherent transport through graphene nanoconstrictions is also robust with respect to variations of constriction geometries and edge defects [3]. This theoretical finding has been recently proved in experiments in graphene nanoconstrictions at low temperature [4,5].…”
Section: Introductionmentioning
confidence: 96%